(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the emergence and development of the realism genre during the Victorian era and its influence on both Western and Eastern literature. Focusing on the theme of orphanhood, the paper compares how this motif is portrayed in the works of English author Charles Dickens and Uzbek writer Gafur Gulyam. Through textual analysis, the study reveals that while both traditions use orphan characters to highlight issues such as poverty, social injustice, and disenfranchisement, their narrative tone and cultural context differ. In Dickens’s works, orphanhood is often tied to industrial capitalism, systemic neglect, and urban misery, reflecting the dark side of the Industrial Revolution. In contrast, Uzbek literature emphasizes moral values, kindness, and the strength of traditional family structures in supporting orphans. The study sheds light on how different societies conceptualize vulnerability and social responsibility through literature.